Research advances in business and management - Gordon, Eric (Wilmington American academic publisher, 2024)
Research advances in business and management involve exploring and understanding business operations, management practices, and strategies through systematic inquiry. This research aims to solve real-world business problems and contribute to the body of knowledge in management. It often involves a multidisciplinary approach, drawing on various fields like marketing, finance, and organizational behavior.
Keywords: Strategic management; Operations management; Business management